The Eurasian miracle. - Goody, Jack (Polity, 2010)
The idea of long-term European dominance is characteristic of most evolutionary theories of human culture and society in the 19th century. It was commonly believed that there was a natural progression from antiquity through feudalism to capitalism which could not have taken place elsewhere. In this book, Jack Goody examines this topic -- Présentation de l'éditeur.